Dynamic Regulation of Extracellular Superoxide Production by the Coccolithophore Emiliania huxleyi (CCMP 374) - Plummer, Sydney; Taylor, Alexander E.; Harvey, Elizabeth L.; Hansel, Colleen M.; Diaz, Julia M. (Frontiers in Microbiology, 2019)
In marine waters, ubiquitous reactive oxygen species (ROS) drive biogeochemical cycling of metals and carbon. Marine phytoplankton produce the ROS superoxide (O2-) extracellularly and can be a dominant source of O2- in natural aquatic systems. However, the cellular regulation, biological functioning, and broader ecological impacts of extracellular O2- production by marine phytoplankton remain mysterious. Here, we explored the regulation and potential roles of extracellular O2- production by a noncalcifying strain of the cosmopolitan coccolithophorid Emiliania huxleyi, a key species of marine phytoplankton that has not been examined for extracellular O2- production previously. Cell-normalized extracellular O2- production was highest under presumably low-stress conditions during active proliferation and inversely related to cell density during exponential phase. Removal of extracellular O2- through addition of the O2- scavenger superoxide dismutase (SOD), however, increased growth rates, growth yields, cell biovolume, and photosynthetic efficiency (Fv/Fm) indicating an overall physiological improvement. Thus, presence of extracellular O2- does not directly stimulate E. huxleyi proliferation, as previously suggested for other phytoplankton, bacteria, fungi, and protists. Extracellular O2- production decreased in the dark, suggesting a connection with photosynthetic processes. Taken together, the tight regulation of this stress independent production of extracellular O2- by E. huxleyi suggests that it could be involved in fundamental photophysiological processes.